Cardiac Signals Are Independently Associated with Temporal Discounting and Time Perception - Fung, Bowen J.; Crone, Damien L.; Bode, Stefan; Murawski, Carsten (Frontiers in Behavioral Neuroscience, 2017)
Cardiac signals reflect the function of the autonomic nervous system and have previously been associated with a range of self-regulatory behaviours such as emotion regulation and memory recall. It is unknown whether cardiac signals may also be associated with self-regulation in the temporal domain, in particular impulsivity. We assessed both decision impulsivity (temporal discounting) and time perception impulsivity (duration reproduction) in 120 participants while they underwent electrocardiography in order to test whether cardiac signals were related to these two aspects of impulsivity. We found that over the entire period of task performance, individuals with higher heart rates had a tendency toward lower discount rates, supporting previous research that has associated sympathetic responses with decreased impulsivity. We also found that low-frequency components of heart rate variability were associated with a less accurate perception of time, suggesting that time perception may be modulated by autonomic nervous system function. Overall, these findings constitute preliminary evidence that autonomic function plays an important role in both decision impulsivity and time perception.